Study on material transfer in the process of contact strips rubbing against a contact wire with electric current. (February 2016) - Hu, Y; Chen, GX; Gao, GQ; Wu, GN; Zhang, WH; Zhou, ZR
A series of experimental tests on a block-on-ring tester were carried out to obtain a new understanding of severe material transfer in the process of contact strips rubbing against a contact wire with electric current. Three types of contact strip materials including an aluminum-based strip, a copper-based strip, and a pure carbon strip are tested in electric sliding against two contact wire materials including a pure copper contact wire and a copper–silver alloy contact wire. Test results show that there are serious material transfers in these three different friction couples in electric sliding. The aluminum-based strip has the severest material transfer, followed by the copper-based strip. The pure carbon strip has the minimum material transfer. It is found that the material transfer increases with the increase of the sliding speed, the arc discharge intensity, and the contact pressure. In the presence of electric current, contact strip materials are always transferred to the contact wire.